2023
DOI: 10.3390/agronomy13020357
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heavy Metal Pollution of Agricultural Soil, Irrigation Water, and Vegetables in and Nearby the Cupriferous City of Lubumbashi, (Democratic Republic of the Congo)

Abstract: Lubumbashi (DR Congo)—the capital of copper mining—has been considered as one of the richest mining regions of the world for more than a decade. These riches have brought along multiple mining companies responsible for soil, river water and vegetable pollution, as in many African cities. The aim of the present study was to quantify and evaluate the pollution levels and the potential sources of soil, irrigation water and vegetable contamination by the metals As, Cd, Cr, Cu, Pb, Co and Zn in the urban gardens of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…Moreover, anthropogenic activities are the primary cause of the pollution of soil and groundwater (Hassan et al, 2021). The production of food crops on these contaminated soils with contaminated irrigation water resulted to the bioaccumulation of potentially toxic substances in plants, which increased significant health risks for people (Riaz et al, 2021;Mununga Katebe et al, 2023). Findings of the current study revealed similar results in which polluted irrigation sources resulted in higher bioaccumulation metals and metalloids in the ridge gourd fruit (Tables 1-3).…”
Section: Correlation Analysissupporting
confidence: 63%
See 1 more Smart Citation
“…Moreover, anthropogenic activities are the primary cause of the pollution of soil and groundwater (Hassan et al, 2021). The production of food crops on these contaminated soils with contaminated irrigation water resulted to the bioaccumulation of potentially toxic substances in plants, which increased significant health risks for people (Riaz et al, 2021;Mununga Katebe et al, 2023). Findings of the current study revealed similar results in which polluted irrigation sources resulted in higher bioaccumulation metals and metalloids in the ridge gourd fruit (Tables 1-3).…”
Section: Correlation Analysissupporting
confidence: 63%
“…The solubility of heavy metals increases with a decrease in pH, leading to higher plant accumulation and absorption. This can pose possible health risks and the health of consumers (Mununga Katebe et al, 2023;Tariq et al, 2023).…”
Section: Correlation Analysismentioning
confidence: 99%
“…Consistent with the concentration values in soils and plants, the results showed a higher proportion of values above the FAO and WHO limits in Penga Penga ( Figure 2 ). In this case, the consumption of mango and S. guineense fruits and leaves may constitute an additional factor for exposure to trace metals, as already reported for other plant products in the region [ 7 , 44 , 45 ]. Nevertheless, calculations of the SWC showed that the consumption of S. guineense fruit is limited to 6.6 kg by the Cd concentration, while it is limited to 9 kg per week for mango flesh (and skin) by the Pb concentration ( Table 5 ).…”
Section: Discussionmentioning
confidence: 58%
“…Natural sources of trace elements are geological formations, weathering of rocks, soil erosion and volcanic activities (Arfaeinia et al, 2019). Anthropogenic sources include mining (Qiao et al, 2023), industrial processes (Long et al, 2021), agricultural practices (Mununga Katebe et al, 2023), wastewater discharge (Xia et al, 2023), surface runoff (Gao et al, 2022), transportation (Faisal et al, 2022), dam construction (Çevik et al, 2009) and many others.…”
Section: Introductionmentioning
confidence: 99%